Rumor cleanup : how easy it is? - Xia, Ji (2013)
Rumor spreading can be considered as a process of “infection of mind” and shares similar spreading dynamics as epidemic. In order to find out the factors that may affect the efficiency of cleaning rumor, this project investigated both the steady state and the time-dependent behavior of cleaning process under different network models. It is found that the total number of infective nodes get cleaned at steady state is not related to the number of edges own by starting node. The nodal degree of starting node only determines how fast the process can reach the steady state. The higher the nodal degree of starting node, the faster the process can reach the steady state. Starting from multiple nodes can make the process be even faster but number of starting nodes is not an influencing factor. For both network, increase spread rate can help to increase the final number of nodes get cleaned, however the change of recovery rate does not have much impact on the cleaning efficiency. As compared with scale free network, random network is more prone to spread information.